Liquid metal interlayer type heat-conducting gel sheet and preparation method thereof
By introducing a liquid metal interlayer into the two-component thermal gel to form a sandwich sandwich structure, the problems of uneven mixing of thermal fillers and excessive viscosity in the single-component thermal gel are solved, and high thermal conductivity and stability are achieved.
Patent Information
- Application Number
- CN202411491875.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-28
AI Technical Summary
During the use of existing single-component thermal conductivity gels, there are problems such as uneven mixing of thermal fillers, excessive viscosity, poor extrusion, difficulty in dispensing and high oil yield, which affects its thermal conductivity and mechanical properties.
A two-component thermal conductivity gel is used to combine the thermal filler and liquid metal is added to the two-component thermal conductivity gel in the form of a sandwich to form a sandwich sandwich structure to improve thermal conductivity and stability.
Thermal gel sheet with high thermal conductivity, low interface thermal resistance, good flexibility, good adhesion and low oil yield are achieved, which improves thermal conductivity and thermal conductivity, while avoiding leakage of liquid metals, ensuring the stability and reliability of the material.
Smart Images

Figure CN119730144A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermally conductive gels, in particular to a liquid metal sandwich type thermally conductive gel sheet and a preparation method thereof. Background Art
[0002] In recent years, with the rapid development of miniaturization and density of microelectronic devices and high power and high frequency of high voltage electrical equipment, it is inevitable that the rapid accumulation of heat will cause the thermal efficiency of the device to run away during use, which will seriously reduce the service life, stability and reliability of electronic equipment and components. Therefore, how to use high-performance thermal interface materials to solve the heat dissipation problem of electronic equipment has become a top priority.
[0003] At present, the widely used thermal interface materials on the market include thermal grease, thermal gasket, thermal gel, thermal phase change material and thermal structural adhesive. They each have their own advantages and disadvantages. Among them, thermal grease is generally paste-like and has fluidity. It is suitable for regular bonding interfaces, but there are problems such as oil separation, difficulty in cleaning, and inconvenient construction; thermal gaskets are in sheet form and suitable for large-area application, but for irregular interfaces, they cannot be completely sealed and bonded. There is a lot of air in the unbonded area, which affects heat conduction; thermal gel combines the advantages of thermal grease and thermal gasket, with excellent thermal conductivity, good bonding effect, high and low temperature resistance, and efficient automatic dispensing process. It has attracted much attention in recent years and is likely to become the main material in the field of thermal conductivity.
[0004] Thermal conductive gels can be divided into single-component thermal conductive gels and two-component thermal conductive gels according to product classification. Single-component thermal conductive gels have the advantages of high thermal conductivity, simple preparation process, wide working range and good thixotropy, and are favored by more and more customers in the thermal conductive industry. However, there are still many problems with the single-component thermal conductive gels on the market: (1) Thermal conductive gels with high thermal conductivity often require the addition of a large amount of thermal conductive fillers, which leads to uneven mixing of the thermal conductive fillers within the polymer matrix and causes performance degradation; (2) The high viscosity of the glue leads to poor extrusion, difficulty in dispensing and high oil yield during electronic packaging, which in turn affects the thermal conductivity and mechanical properties of the thermal conductive gel after curing.
[0005] In view of the above problems, it is of great significance to develop a two-component thermally conductive gel sheet with high thermal conductivity, low interface thermal resistance, good flexibility, good adhesion and low oil yield. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention adopts a two-component thermally conductive gel, compounds the thermally conductive filler, and adds liquid metal in the form of an interlayer between the two-component thermally conductive gels, thereby preparing a thermally conductive gel sheet with high thermal conductivity, low interface thermal resistance, good flexibility, good adhesion and low oil yield.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention provides a liquid metal sandwich thermally conductive gel sheet, which has a sandwich structure, wherein the upper and lower layers are thermally conductive gel layers, and the middle layer is a phase change material sandwich; the thermally conductive gel layer is made of thermally conductive gel, and the phase change material sandwich is made of liquid metal; the thermally conductive gel is obtained by mixing component A and component B; the component A comprises the following component raw materials: double-terminal vinyl polydimethylsiloxane, double hydrogen bond functional polydimethylsiloxane, filler one, styrene-based siloxane, end-group modified polyhedral oligomeric silsesquioxane, a compatibilizer, and an antioxidant; the component B comprises the following component raw materials: double-terminal vinyl polydimethylsiloxane, double hydrogen bond functional polydimethylsiloxane, a catalyst, liquid rubber, filler two, liquid crystal epoxy resin, end-group modified polydiphenylsiloxane, surface modifier grafted nano core-shell structure powder, a compatibilizer, and an antioxidant.
[0009] In some embodiments of the present invention, the mass ratio of thermally conductive gel to liquid metal in the thermally conductive gel sheet is 1 to 5:1, and the coverage area percentage of liquid metal on the thermally conductive gel layer is 60% to 80%; the mass ratio of component A to component B in the thermally conductive gel is 1:1.
[0010] In some embodiments of the present invention, the liquid metal is any one of a single metal, a binary alloy, a ternary alloy or a multi-element alloy, and its melting point is any one or more of 11°C, 16°C, 25°C, 30°C, 47°C, 60°C, and 75°C.
[0011] In some embodiments of the present invention, the weight percentages of the raw materials included in component A are: 69-97 parts of double-terminated vinyl polydimethylsiloxane, 18-46 parts of double hydrogen-bonded functional polydimethylsiloxane, 200-1300 parts of filler, 0.1-5 parts of styrene-based siloxane, 1-13 parts of terminal-modified polyhedral oligomeric silsesquioxane, 1-20 parts of compatibilizer, and 0.1-0.5 parts of antioxidant; the weight percentages of the raw materials included in component B are: The invention comprises: 54-82 parts of double-terminated vinyl polydimethylsiloxane, 18-46 parts of double hydrogen bond functional polydimethylsiloxane, 0.5-7 parts of catalyst, 0.3-19 parts of liquid rubber, 100-1200 parts of filler, 0.1-21 parts of liquid crystal epoxy resin, 0.1-3 parts of terminal-modified polydiphenylsiloxane, 1-3 parts of nano core-shell structure powder grafted with surface modifier, 1-20 parts of compatibilizer and 0.1-0.5 parts of antioxidant.
[0012] In some embodiments of the present invention, the filler 1 includes nanofillers and inorganic functional fillers; the filler 2 includes inorganic functional fillers; the nanofillers are selected from one-dimensional nanofillers; the inorganic functional fillers include any one or more of graphite, inorganic oxides, and metal powders with a regular polyhedral structure or a spherical morphology.
[0013] The second aspect of the present invention provides a method for preparing the above-mentioned liquid metal sandwich thermally conductive gel sheet, comprising the following steps:
[0014] Step 1: Put component A and component B into a mixing tube respectively, mix them evenly according to the proportion through a dispensing machine, and dispense them on the substrate to obtain the first layer of thermal conductive gel;
[0015] Step 2: Printing liquid metal on the first layer of thermal conductive gel by screen printing to obtain a liquid metal interlayer;
[0016] Step 3: Repeat the operation of step 1 to obtain a second layer of thermally conductive gel, that is, a liquid metal sandwich thermally conductive gel sheet.
[0017] In some embodiments of the present invention, the preparation method of component A comprises the following steps:
[0018] (a) mixing the double-terminal vinyl polydimethylsiloxane, the double hydrogen-bond functional polydimethylsiloxane, the styryl siloxane, the terminal-modified polyhedral oligomeric silsesquioxane and the compatibilizer by a high-speed disperser to obtain a first mixture;
[0019] (b) pouring the first mixture into a planetary mixer, adding nanofiller, and stirring evenly to obtain a second mixture;
[0020] (c) adding the inorganic functional filler into a planetary mixer three times and stirring evenly after each addition;
[0021] (d) adding an antioxidant, vacuum extraction, and stirring to obtain component A.
[0022] In some embodiments of the present invention, the preparation method of component B comprises the following steps:
[0023] 1) mixing double-terminal vinyl polydimethylsiloxane, double hydrogen-bond functional polydimethylsiloxane, catalyst, liquid rubber, liquid crystal epoxy resin, terminal-modified polydiphenylsiloxane, surface modifier-grafted nano core-shell structure powder and compatibilizer in a high-speed disperser to obtain a third mixture;
[0024] 2) Pour the third mixture into a planetary mixer, and add the inorganic functional filler into the planetary mixer three times, stirring evenly after each addition;
[0025] 3) Add antioxidant, stir evenly, and extract under vacuum to obtain component B.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. Since the filler and the matrix cannot be in completely close contact, there are gaps inside the thermally conductive gel. The thermally conductive gel sheet provided by the present invention has a sandwich structure, with a liquid metal interlayer between two layers of thermally conductive gel. The liquid metal can fill the interior of the thermally conductive gel, eliminating the tiny pores inside the single component of the thermally conductive gel, thereby further reducing the contact thermal resistance between the internal components and improving the thermal conductivity of the thermally conductive gel sheet. At the same time, the addition of liquid metal further improves the thermal conductivity of the thermally conductive gel sheet. The sandwich thermally conductive gel sheet provided by the present invention can prevent the possible leakage of liquid metal during use, thereby ensuring the stability and reliability of the thermal interface material.
[0028] 2. In the thermally conductive gel sheet provided by the present invention, thermally conductive fillers of different sizes and shapes with high thermal conductivity are selected for compounding during the preparation process of the thermally conductive gel, thereby effectively improving the filling rate of the thermally conductive filler and optimizing the fluidity of the individual components in the thermally conductive gel before curing, which is beneficial to the formation of a thermally conductive path, thereby improving the overall thermal conductivity of the thermally conductive gel.
[0029] 3. Different from single-component thermally conductive gel, the two-component thermally conductive gel used in the thermally conductive gel sheet provided by the present invention has a low oil yield and will not leak grease during the curing process, thereby being able to keep the interface clean and at the same time being able to fit tightly to uneven interfaces to achieve more efficient heat conduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The figure is a schematic diagram of the structure of a liquid metal sandwich thermally conductive gel sheet according to an embodiment of the present invention.
[0031] Reference numerals:
[0032] 1-first layer of thermal conductive gel; 2-liquid metal interlayer; 3-second layer of thermal conductive gel. DETAILED DESCRIPTION
[0033] The liquid metal sandwich thermally conductive gel sheet of the present invention and its preparation method are described in detail below.
[0034] When optimizing the thermal conductivity of the thermally conductive gel and improving its comprehensive performance, the inventors of the present invention used liquid metal to fill the middle of two layers of thermally conductive gel to form a liquid metal sandwich thermally conductive gel sheet. This not only improves the thermal conductivity of the thermally conductive gel sheet, but also prevents possible leakage of the liquid metal during use. On this basis, the present invention was completed.
[0035] The first aspect of the present invention provides a liquid metal sandwich thermally conductive gel sheet, which has a sandwich structure, wherein the upper and lower layers are thermally conductive gel layers, and the middle layer is a phase change material sandwich; the thermally conductive gel layer is made of thermally conductive gel, and the phase change material sandwich is made of liquid metal; the thermally conductive gel is obtained by mixing component A and component B; the component A comprises the following component raw materials: double-terminal vinyl polydimethylsiloxane, double hydrogen bond functional polydimethylsiloxane, filler one, styrene-based siloxane, end-group modified polyhedral oligomeric silsesquioxane, a compatibilizer, and an antioxidant; the component B comprises the following component raw materials: double-terminal vinyl polydimethylsiloxane, double hydrogen bond functional polydimethylsiloxane, a catalyst, liquid rubber, filler two, liquid crystal epoxy resin, end-group modified polydiphenylsiloxane, surface modifier grafted nano core-shell structure powder, a compatibilizer, and an antioxidant.
[0036] The liquid metal sandwich thermally conductive gel sheet provided by the present invention has a sandwich structure. Figure 1 As shown, the liquid metal is filled between two layers of thermally conductive gel in the form of a sandwich, which can fill the tiny pores inside the thermally conductive gel, improve the thermal conductivity of the thermally conductive gel sheet, and prevent the liquid metal from leaking. In the present invention, the shape and thickness of the thermally conductive gel sheet are not particularly limited and can be adjusted according to application requirements, such as Figure 1 In some specific implementations of the present invention, the thickness of the thermally conductive gel sheet may be 0.2-5.0 mm, 0.2-0.4 mm, 0.4-0.6 mm, 0.6-0.8 mm, 0.8-1.0 mm, 1.0-2.0 mm, 2.0-3.0 mm, 3.0-4.0 mm, or 4.0-5.0 mm.
[0037] In some embodiments of the present invention, the mass ratio of the thermally conductive gel to the liquid metal in the thermally conductive gel sheet is 1 to 5:1, that is, the mass ratio of the thermally conductive gel to the liquid metal can be 5:1, 4.5:1, 4:1, 3.5:1, 3:1, 2.5:1, 2:1, 1:1, etc. When the amount of liquid metal added is too small, the improvement of the thermal conductivity of the prepared thermally conductive gel sheet is not obvious; when the amount added is too much, the prepared thermally conductive gel sheet will be relatively hard and easy to conduct electricity. Therefore, the liquid metal is selectively added according to the needs of use in the specific implementation, and is used to improve the thermal conductivity of the thermally conductive gel sheet after addition. The coverage area percentage of the liquid metal on the thermally conductive gel layer is 60% to 80%; the mass ratio of component A to component B in the thermally conductive gel is 1:1.
[0038] As a phase-change metal material, liquid metal has a thermal conductivity much higher than that of non-metallic media, so its heat conduction and transportation capabilities are extremely efficient, and its boiling point exceeds 2000°C, it is resistant to high temperatures, there is no risk of boiling and evaporation, and it is stable, reliable and non-toxic. In some embodiments of the present invention, the liquid metal is any one of a single metal, a binary alloy, a ternary alloy or a multi-element alloy, and its melting point is any one or more of 11°C, 16°C, 25°C, 30°C, 47°C, 60°C, and 75°C. In some specific embodiments of the present invention, the elemental metal is selected from any one of gallium, indium, tin, mercury, and cesium; the binary alloy is selected from any one of gallium-indium alloy, gallium-tin alloy, gallium-mercury alloy, gallium-cesium alloy, and tin-indium alloy; the ternary alloy is selected from any one of gallium-indium-tin alloy, gallium-indium-mercury alloy, gallium-indium-cesium alloy, gallium-tin-mercury alloy, gallium-tin-cesium alloy, gallium-mercury-cesium alloy, gallium-sodium-potassium alloy, and tin-indium-tin alloy; the multi-component alloy is one of the low-melting-point multi-component alloys prepared by any one or more of gallium, tin, silver, copper, aluminum or chromium and any one of the above-mentioned ternary alloys.
[0039] In some embodiments of the present invention, the weight percentages of the raw materials included in component A are: 69-97 parts of double-terminated vinyl polydimethylsiloxane, 18-46 parts of double hydrogen-bonded functional polydimethylsiloxane, 200-1300 parts of filler, 0.1-5 parts of styrene-based siloxane, 1-13 parts of terminal-modified polyhedral oligomeric silsesquioxane, 1-20 parts of compatibilizer, and 0.1-0.5 parts of antioxidant; the weight percentages of the raw materials included in component B are: The invention comprises: 54-82 parts of double-terminated vinyl polydimethylsiloxane, 18-46 parts of double hydrogen bond functional polydimethylsiloxane, 0.5-7 parts of catalyst, 0.3-19 parts of liquid rubber, 100-1200 parts of filler, 0.1-21 parts of liquid crystal epoxy resin, 0.1-3 parts of terminal-modified polydiphenylsiloxane, 1-3 parts of nano core-shell structure powder grafted with surface modifier, 1-20 parts of compatibilizer and 0.1-0.5 parts of antioxidant.
[0040] In some embodiments of the present invention, the viscosity of the dual-terminated vinyl polydimethylsiloxane at 25° C. is 50 to 550 mPa·s, and the vinyl content is 0.3 to 0.45 wt %.
[0041] In some embodiments of the present invention, the filler 1 includes a nanofiller and an inorganic functional filler; the nanofiller is selected from a one-dimensional nanofiller; the nanofiller is selected from a one-dimensional nanofiller with a length of 10 to 100 μm and a diameter of 10 to 100 nm, and the one-dimensional nanofiller includes but is not limited to any one or more of carbon nanotubes, nanosilver wires, and nanozinc oxide wires; in some embodiments of the present invention, the filler 2 includes an inorganic functional filler; preferably, in the filler 1 and filler 2 of the present invention, the inorganic functional filler includes any one or more of graphite, inorganic oxides, and metal powders with a regular polyhedral structure or a spherical shape; the inorganic functional filler Including but not limited to any one or more of aluminum oxide, aluminum nitride, boron nitride, diamond, and aluminum hydroxide; the particle size of aluminum oxide is selected from one or more of 0.2μm, 1μm, 10μm, 40μm, 70μm, and 120μm; the particle size of aluminum nitride is selected from one or more of 0.2μm, 1μm, 10μm, 40μm, 80μm, and 120μm; the lateral size of boron nitride is selected from one or more of 1μm, 5μm, 10μm, and 20μm; the particle size of diamond is selected from one or more of 1μm, 5μm, 10μm, 40μm, and 70μm; the particle size of aluminum hydroxide is selected from one or more of 1μm, 10μm, and 30μm.
[0042] In the present invention, styrene-based siloxane is mainly used as a surfactant and to reduce the viscosity of the overall material. In some embodiments of the present invention, the viscosity of the styrene-based siloxane is 10-300 cps, which can be 10-20 cps, 20-40 cps, 40-60 cps, 60-80 cps, 80-100 cps, 100-150 cps, 150-200 cps, 200-250 cps, 250-300 cps, preferably 10-100 cps.
[0043] In some embodiments of the present invention, the modified groups of the terminal-modified polyhedral oligomeric silsesquioxane include, but are not limited to, any one of silanol, carboxyalkyl, amide, vinyl, amino, methoxy, ethoxy, and silane.
[0044] The compatibilizer can increase the adhesion between the polymer matrix and other solid components such as thermal conductive fillers, act as a bridge, and help form an effective heat conduction path, thereby reducing the contact thermal resistance between the thermal conductive fillers. In some embodiments of the present invention, the compatibilizer includes but is not limited to any one or more of silane coupling agents, silane ester coupling agents, titanate coupling agents, aluminate coupling agents, and borate coupling agents. The antioxidant includes but is not limited to any one or two of antioxidant 1010 and antioxidant 1076.
[0045] In some embodiments of the present invention, the catalyst includes but is not limited to any one or more of divinyltetramethyldisiloxane platinum complex, divinyloctamethyltetrasiloxane platinum complex, and peroxide.
[0046] In some embodiments of the present invention, the liquid rubber includes but is not limited to any one or more of liquid butadiene rubber, liquid acrylic rubber, and liquid EPDM rubber, and its viscosity is 50-2500cps, which can be 50-100cps, 100-200cps, 200-400cps, 400-1000cps, 1000-1500cps, 1500-2000cps, or 2000-2500cps.
[0047] In some embodiments of the present invention, the liquid crystal epoxy resin includes any one or both of biphenyl type liquid crystal epoxy resin and aromatic ester type liquid crystal epoxy resin.
[0048] In some embodiments of the present invention, the terminal-modified polydiphenylsiloxane is a polystyrene siloxane containing olefin groups, terminal hydroxyl groups or silanol groups at both ends, and has a viscosity of 10 to 50 cps, which mainly plays the role of reducing viscosity and assisting reaction.
[0049] In some embodiments of the present invention, the surface modifier grafted nano core-shell structure powder is a nano spherical powder particle with non-polar groups on the surface, wherein the non-polar groups include silane groups, CC chain groups, -CH3 groups and amino groups that can participate in the reaction, and are formed by coating the polymer material with the above non-polar groups on the surface of the powder particles through an emulsion preparation method. The powder particles in these nano spherical powder particles are any one of aluminum oxide, silicon oxide, and magnesium oxide, and the particle size of the powder particles is 10 to 100 nm.
[0050] A second aspect of the present invention provides a method for preparing the above-mentioned liquid metal sandwich thermally conductive gel sheet, comprising the following steps:
[0051] Step 1: Put component A and component B into a mixing tube respectively, mix them evenly according to the proportion through a dispensing machine, and dispense them on the substrate to obtain the first layer of thermal conductive gel 1;
[0052] Step 2: Printing liquid metal on the first layer of thermal conductive gel 1 by screen printing to obtain a liquid metal interlayer 2;
[0053] Step 3: Repeat the operation of step 1 to obtain a second layer of thermally conductive gel 3, that is, a liquid metal sandwich thermally conductive gel sheet.
[0054] In the present invention, the coverage area and thickness of the liquid metal on the first layer of thermally conductive gel 1 can be adjusted by regulating the parameters of screen printing, thereby ensuring that the liquid metal does not leak during the use of the thermally conductive gel sheet.
[0055] In some embodiments of the present invention, component A and component B are uniformly mixed in a mass ratio of 1:1 by a dispensing machine.
[0056] In some embodiments of the present invention, the dispensing is performed in a certain shape; there is no special restriction on the shape type and thickness of the shape, which can be adjusted according to application requirements, for example, it can be round, square, long strip, irregular shape, etc.
[0057] In some embodiments of the present invention, the substrate is an aluminum plate.
[0058] In some embodiments of the present invention, the preparation method of component A comprises the following steps:
[0059] (a) mixing the double-terminal vinyl polydimethylsiloxane, the double hydrogen-bond functional polydimethylsiloxane, the styryl siloxane, the terminal-modified polyhedral oligomeric silsesquioxane and the compatibilizer by a high-speed disperser to obtain a first mixture;
[0060] (b) pouring the first mixture into a planetary mixer, adding nanofiller, and stirring evenly to obtain a second mixture;
[0061] (c) adding the inorganic functional filler into a planetary mixer three times and stirring evenly after each addition;
[0062] (d) adding an antioxidant, vacuum extraction, and stirring to obtain component A.
[0063] In some embodiments of the present invention, in step (a), the material temperature during mixing is 20-30°C, preferably 25°C, the stirring rate is 1000-2000 rpm, and the stirring time is 15-25 min, preferably the stirring rate is 1500 rpm and the stirring time is 20 min.
[0064] In some embodiments of the present invention, in step (b), the material temperature during stirring is 20-30°C, preferably 25°C, the stirring rate is 200-300 rpm, and the stirring time is 10-14 min, preferably the stirring rate is 250 rpm and the stirring time is 12 min.
[0065] In some embodiments of the present invention, in step (c), the material temperature during stirring is 20-30°C, preferably 25°C, the stirring rate is 200-300 rpm each time, and the stirring time is 20-30 min each time, preferably the stirring rate is 250 rpm each time, and the stirring time is 25 min each time.
[0066] In some embodiments of the present invention, in step (d), the material temperature during stirring is 20-30°C, preferably 25°C, the stirring rate is 400-500 rpm, and the stirring time is 30-40 min, preferably the stirring rate is 450 rpm, and the stirring time is 35 min.
[0067] In some embodiments of the present invention, in step (d), the vacuum degree of the vacuum extraction is below -0.08 MPa.
[0068] In some embodiments of the present invention, the preparation method of component B comprises the following steps:
[0069] 1) mixing double-terminal vinyl polydimethylsiloxane, double hydrogen-bond functional polydimethylsiloxane, catalyst, liquid rubber, liquid crystal epoxy resin, terminal-modified polydiphenylsiloxane, surface modifier-grafted nano core-shell structure powder and compatibilizer in a high-speed disperser to obtain a third mixture;
[0070] 2) Pour the third mixture into a planetary mixer, and add the inorganic functional filler into the planetary mixer three times, stirring evenly after each addition;
[0071] 3) Add antioxidant, stir evenly, and extract under vacuum to obtain component B.
[0072] In some embodiments of the present invention, in step 1), the material temperature during the mixing process is 20-30°C, preferably 25°C, the stirring rate is 1000-2000 rpm, the stirring time is 15-25 min, preferably the stirring rate is 1500 rpm, and the stirring time is 20 min;
[0073] In some embodiments of the present invention, in step 2), the material temperature during stirring is 20-30°C, preferably 25°C, the stirring rate is 200-300 rpm each time, and the stirring time is 20-30 min each time, preferably the stirring rate is 250 rpm each time, and the stirring time is 25 min each time;
[0074] In some embodiments of the present invention, in step 3), the material temperature during stirring is 20-30°C, preferably 25°C, the stirring rate is 400-500 rpm, the stirring time is 30-40 min, preferably the stirring rate is 450 rpm, and the stirring time is 35 min.
[0075] In some embodiments of the present invention, in step 3), the vacuum degree of the vacuum extraction is below -0.08 MPa.
[0076] The specific embodiments of the present invention are further described in detail below in conjunction with preferred embodiments. When the embodiments provide numerical ranges, it should be understood that, unless otherwise specified in the present invention, the two endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, as those skilled in the art grasp the prior art and record the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0077] Example 1
[0078] 1. The raw material composition of liquid metal sandwich thermal conductive gel sheet is as follows:
[0079] 8 parts of liquid metal gallium indium tin alloy (melting point 11°C);
[0080] The weight proportions of the raw materials of each component in component A are as follows: 69 parts of double-terminated vinyl polydimethylsiloxane (molecular weight 5000), 18 parts of double hydrogen bond functional polydimethylsiloxane (molecular weight 2000), 0.1 parts of styrene siloxane (viscosity 50cps), 1 part of terminal modified polyhedral oligomeric silsesquioxane, 1 part of compatibilizer, 8 parts of carbon nanotubes (length 10μm, diameter 10nm), 50 parts of spherical alumina powder (particle size 0.2μm), 100 parts of spherical alumina powder (particle size 1μm), 150 parts of spherical alumina powder (particle size 10μm), and 10100.1 parts of antioxidant;
[0081] The weight proportions of the raw materials of each component in component B are as follows: 54 parts of double-terminated vinyl polydimethylsiloxane (molecular weight of 5000), 18 parts of double hydrogen bond functional polydimethylsiloxane (molecular weight of 2000), 0.5 parts of catalyst divinyl octamethyl tetrasiloxane platinum complex, 1 part of liquid butadiene rubber (viscosity of 50 cps), 50 parts of spherical alumina powder (particle size of 0.2 μm), 100 parts of spherical alumina powder (particle size of 1 μm), 150 parts of spherical alumina powder (particle size of 10 μm), 1 part of biphenyl type liquid crystal epoxy resin, 1 part of terminal hydroxyl polydiphenylsiloxane (viscosity of 10 cps), 1 part of 5 nanometer polymethylsilane coated modified alumina, 1 part of compatibilizer, and 10760.1 parts of antioxidant.
[0082] 2. Preparation of Liquid Metal Sandwich Thermally Conductive Gel Sheet
[0083] 2.1 Preparation of component A:
[0084] (1) 69 parts of double-terminated vinyl polydimethylsiloxane (molecular weight of 5000), 18 parts of double hydrogen-bonded functional polydimethylsiloxane (molecular weight of 2000), 0.1 parts of styrene-based siloxane (viscosity of 50 cps), 1 part of terminal-modified polyhedral oligomeric silsesquioxane, and 1 part of a compatibilizer are added to a high-speed disperser and mixed evenly. During the mixing process, the temperature of the raw materials is controlled at 25° C., the stirring rate is 1500 rpm, and the stirring time is 20 min to obtain a first mixture.
[0085] (2) The first mixture was poured into a planetary mixer, and then 8 parts of carbon nanotubes (length 10 μm, diameter 10 nm) were added. During the stirring process, the raw material temperature was controlled to be 25° C., the stirring speed was 250 rpm, and the stirring time was 12 min to obtain a second mixture.
[0086] (3) 50 parts of spherical alumina powder (particle size of 0.2 μm), 100 parts of spherical alumina powder (1 μm), and 150 parts of spherical alumina powder (10 μm) are mixed and divided into three parts. One part at a time is added to the planetary mixer three times, and the following conditions are used for stirring after each addition: during the stirring process, the raw material temperature is controlled at 25°C, the stirring speed is 250 rpm, and the stirring time is 25 min.
[0087] (4) After the powder is added, 10100.1 parts of antioxidant is added and vacuum extraction is performed. The vacuum degree is below -0.08 MPa. The raw material temperature is controlled at 25°C, the stirring speed is 450 rpm, and the stirring time is 35 min to obtain component A.
[0088] 2.2 Preparation of component B:
[0089] (1) Take 54 parts by weight of double-terminated vinyl polydimethylsiloxane (molecular weight of 5000), 18 parts of double hydrogen bond functional polydimethylsiloxane (molecular weight of 2000), 0.5 parts of catalyst divinyl octamethyl tetrasiloxane platinum complex, 1 part of liquid butadiene rubber (viscosity of 50 cps), 1 part of biphenyl type liquid crystal epoxy resin, 1 part of terminal hydroxyl polydiphenylsiloxane (viscosity of 10 cps), 1 part of 5 nanometer polymethylsilane coated modified alumina and 1 part of compatibilizer, add the above raw materials into a high-speed disperser, mix well, control the raw material temperature at 25°C during mixing, and stir at 1500 rpm for 20 minutes to obtain a third mixture.
[0090] (2) Pour the third mixture into a planetary mixer, then mix 50 parts of spherical alumina powder (particle size of 0.2 μm), 100 parts of spherical alumina powder (particle size of 1 μm), and 150 parts of spherical alumina powder (particle size of 10 μm), and divide them into three parts, one part at a time, three times in total, and stir them after each addition under the following conditions: control the raw material temperature to 25°C, the stirring speed to 250 rpm, and stir for 25 minutes.
[0091] (3) After the powder is added, 10761 parts of antioxidant is added and stirred. The raw material temperature is controlled at 25°C and the stirring speed is 450 rpm. Stir for 35 minutes until the raw materials are stirred evenly. Then vacuum extraction is performed and the vacuum degree is below -0.08 MPa to obtain component B.
[0092] 2.3 Preparation of thermally conductive gel sheet
[0093] Step 1: Put 200 mL of component A and 200 mL of component B into the A and B rubber tubes respectively, mix them evenly with an automatic dispensing machine at a mass ratio of 1:1, and dispense them onto the aluminum plate at a speed of 15 mm / s to obtain the first layer of thermal conductive gel 1;
[0094] Step 2: 8 portions of liquid metal gallium indium tin alloy (melting point 11° C.) are printed on the first layer of thermal conductive gel 1 by screen printing to obtain a liquid metal interlayer 2, wherein the coverage area of the liquid metal interlayer 2 on the first layer of thermal conductive gel 1 is 65%;
[0095] Step 3: Repeat the operation of step 1 to obtain a second layer of thermal conductive gel 3, such as Figure 1 As shown, a liquid metal sandwich thermally conductive gel sheet is obtained.
[0096] Example 2
[0097] 1. The raw material composition of liquid metal sandwich thermal conductive gel sheet is as follows:
[0098] 18 parts of liquid metal gallium-indium alloy (melting point 16°C);
[0099] The weight proportions of the raw materials of each component in component A are as follows: 83 parts of double-terminated vinyl polydimethylsiloxane (molecular weight 6000), 32 parts of double hydrogen bond functional polydimethylsiloxane (molecular weight 2000), 2 parts of styrene siloxane (viscosity 50cps), 6 parts of terminal modified polyhedral oligomeric silsesquioxane, 10 parts of compatibilizer, 8 parts of carbon nanotubes (length 10μm, diameter 10nm), 100 parts of spherical alumina powder (particle size 0.2μm), 300 parts of spherical alumina powder (particle size 1μm), 500 parts of spherical alumina powder (particle size 10μm), and 10100.3 parts of antioxidant;
[0100] The weight proportions of the raw materials of each component in component B are as follows: 68 parts of double-terminated vinyl polydimethylsiloxane (molecular weight of 5000), 32 parts of double hydrogen bond functional polydimethylsiloxane (molecular weight of 2000), 3 parts of catalyst divinyl octamethyl tetrasiloxane platinum complex, 12 parts of liquid butadiene rubber (viscosity of 50cps), 100 parts of spherical alumina powder (particle size of 0.2μm), 300 parts of spherical alumina powder (particle size of 1μm), 500 parts of spherical alumina powder (particle size of 10μm), 10 parts of biphenyl type liquid crystal epoxy resin, 1.5 parts of terminal hydroxyl polydiphenylsiloxane (viscosity of 10cps), 2 parts of 5 nanometer polymethylsilane coated modified alumina, 10 parts of compatibilizer, and 10760.25 parts of antioxidant.
[0101] 2. Preparation of Liquid Metal Sandwich Thermally Conductive Gel Sheet
[0102] The preparation method of the above-mentioned liquid metal sandwich thermally conductive gel sheet is the same as that of Example 1.
[0103] Example 3
[0104] 1. The raw material composition of liquid metal sandwich thermal conductive gel sheet is as follows:
[0105] 14 parts of liquid gallium metal (melting point 30°C);
[0106] The weight proportions of the raw materials of each component in component A are as follows: 94 parts of double-terminated vinyl polydimethylsiloxane (molecular weight of 5000), 46 parts of double hydrogen-bonded functional polydimethylsiloxane (molecular weight of 2000), 5 parts of styrene-based siloxane (viscosity of 50 cps), 13 parts of terminal-modified polyhedral oligomeric silsesquioxane, 20 parts of a compatibilizer, 8 parts of carbon nanotubes (length of 10 μm, diameter of 10 nm), 200 parts of spherical alumina powder (particle size of 0.2 μm), 400 parts of spherical alumina powder (particle size of 1 μm), 500 parts of spherical alumina powder (particle size of 10 μm), and 10100.5 parts of an antioxidant;
[0107] The weight proportions of the raw materials of each component in component B are as follows: 80 parts of double-terminated vinyl polydimethylsiloxane (molecular weight of 5000), 46 parts of double hydrogen bond functional polydimethylsiloxane (molecular weight of 2000), 7 parts of catalyst divinyl octamethyl tetrasiloxane platinum complex, 19 parts of liquid butadiene rubber (viscosity of 50cps), 200 parts of spherical alumina powder (particle size of 0.2μm), 400 parts of spherical alumina powder (particle size of 1μm), 500 parts of spherical alumina powder (particle size of 10μm), 21 parts of biphenyl type liquid crystal epoxy resin, 3 parts of terminal hydroxyl polydiphenylsiloxane (viscosity of 10cps), 3 parts of 5 nanometer polymethylsilane coated modified alumina, 20 parts of compatibilizer, and 10760.5 parts of antioxidant.
[0108] 2. Preparation of Liquid Metal Sandwich Thermally Conductive Gel Sheet
[0109] The preparation method of the above-mentioned liquid metal sandwich thermally conductive gel sheet is the same as that of Example 1.
[0110] Comparative Example 1
[0111] Commercially available silicone thermally conductive gel, free of liquid metal.
[0112] Comparative Example 2
[0113] A thermally conductive gel sheet, wherein the raw materials and proportions of the components are the same as those of Example 2, and the sheet is a non-sandwich structure.
[0114] The preparation method of component A and component B is the same as that of Example 2, except that, during the preparation of the thermally conductive gel sheet, liquid metal is added after component A and component B are mixed to prepare the thermally conductive gel sheet.
[0115] Comparative Example 3
[0116] A thermally conductive gel sheet, wherein spherical alumina powders with a particle size of 0.2 μm and 10 μm are replaced with spherical alumina powders with a particle size of 1 μm in the same weight fraction, and the other raw materials and proportions of the components are the same as those in Example 2.
[0117] The preparation method of the thermally conductive gel sheet is the same as that of Example 2.
[0118] The thermally conductive gel sheet products prepared in the above-mentioned embodiments and comparative examples were tested for hardness, thermal conductivity, thermal resistance and tensile strength. The test results are shown in Table 1 below.
[0119] Table 1 Test results of examples and comparative examples
[0120]
[0121]
[0122] It can be seen from the test data corresponding to the samples obtained from the above embodiments and comparative examples that embodiments 1 to 3 of the present invention all have relatively low hardness, high thermal conductivity, low thermal resistance and high tensile strength, and thus have good thermal conductivity and the ability to resist impact and vibration loads. In Comparative Example 1, no liquid metal was added, and the hardness was higher, the tensile strength was decreased, and the thermal conductivity was significantly lower than that of Example 2, indicating that liquid metal helps to improve the thermal conductivity of the thermally conductive gel sheet and its ability to resist impact and vibration loads; in Comparative Example 2, liquid metal was added, but the sandwich structure was not adopted, and the thermal conductivity was significantly lower than that of Example 2, indicating that the sandwich structure can significantly improve the thermal conductivity of the thermally conductive gel sheet; in Comparative Example 3, compared with Example 2, spherical alumina powders of different particle sizes were replaced with spherical alumina powders of the same particle size and the same weight fraction, and the thermal conductivity of the thermally conductive gel sheet decreased. The reason for this is that when mixed thermally conductive fillers of different particle sizes are used, the filling rate of the thermally conductive filler in the thermally conductive gel can be increased compared with thermally conductive fillers of the same particle size, thereby improving the fluidity of individual components in the thermally conductive gel before curing, forming more thermally conductive pathways, and thus improving the overall thermal conductivity of the thermally conductive gel.
[0123] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A liquid metal sandwich thermally conductive gel sheet, characterized in that: The thermally conductive gel sheet has a sandwich structure, wherein the upper and lower layers are thermally conductive gel layers, and the middle layer is a phase change material interlayer; the thermally conductive gel layer is made of thermally conductive gel, and the phase change material interlayer is made of liquid metal; the thermally conductive gel is obtained by mixing component A and component B; the component A comprises the following component raw materials: double-terminal vinyl polydimethylsiloxane, double hydrogen bond functional polydimethylsiloxane, filler one, styrene-based siloxane, end-group modified polyhedral oligomeric silsesquioxane, a compatibilizer, and an antioxidant; the component B comprises the following component raw materials: double-terminal vinyl polydimethylsiloxane, double hydrogen bond functional polydimethylsiloxane, a catalyst, liquid rubber, filler two, liquid crystal epoxy resin, end-group modified polydiphenylsiloxane, surface modifier grafted nano core-shell structure powder, a compatibilizer, and an antioxidant.
2. The liquid metal sandwich thermally conductive gel sheet according to claim 1, characterized in that: Includes one or more of the following characteristics: (1) The mass ratio of the thermally conductive gel to the liquid metal in the thermally conductive gel sheet is 1 to 5:1; the mass ratio of component A to component B in the thermally conductive gel is 1:1; (2) The liquid metal is any one of a single metal, a binary alloy, a ternary alloy or a multi-element alloy, and its melting point is any one or more of 11°C, 16°C, 25°C, 30°C, 47°C, 60°C, and 75°C; (3) The weight proportions of the raw materials included in component A are: 69-97 parts of double-terminated vinyl polydimethylsiloxane, 18-46 parts of double hydrogen bond functional polydimethylsiloxane, 200-1300 parts of filler, 0.1-5 parts of styrene-based siloxane, 1-13 parts of terminal modified polyhedral oligomeric silsesquioxane, 1-20 parts of compatibilizer, and 0.1-0.5 parts of antioxidant; the weight proportions of the raw materials included in component B are: 54-82 parts of vinyl polydimethylsiloxane, 18-46 parts of double hydrogen bond functional polydimethylsiloxane, 0.5-7 parts of catalyst, 0.3-19 parts of liquid rubber, 100-1200 parts of filler, 0.1-21 parts of liquid crystal epoxy resin, 0.1-3 parts of terminal modified polydiphenylsiloxane, 1-3 parts of nano core-shell structure powder grafted with surface modifier, 1-20 parts of compatibilizer, and 0.1-0.5 parts of antioxidant; (4) The viscosity of the dual-terminated vinyl polydimethylsiloxane at 25° C. is 50 to 550 mPa·s, and the vinyl content is 0.3 to 0.45 wt %; (5) The filler 1 includes a nanofiller and an inorganic functional filler; the filler 2 includes an inorganic functional filler; the nanofiller is selected from a one-dimensional nanofiller; the inorganic functional filler includes any one or more of graphite, inorganic oxides, and metal powders having a regular polyhedral structure or a spherical shape; (6) The viscosity of the styrene siloxane is 10 to 300 cps; (7) The modified group of the terminal-modified polyhedral oligomeric silsesquioxane is selected from any one of silanol, carboxyalkyl, amide, vinyl, amino, methoxy, ethoxy, and silane groups; (8) The compatibilizer is selected from any one or more of silane coupling agents, silane ester coupling agents, titanate coupling agents, aluminate coupling agents, and borate coupling agents; (9) The antioxidant is selected from any one or two of antioxidant 1010 and antioxidant 1076; (10) The catalyst is selected from any one or more of divinyltetramethyldisiloxane platinum complex, divinyloctamethyltetrasiloxane platinum complex, and peroxide; (11) The liquid rubber is selected from any one or more of liquid butadiene rubber, liquid acrylic rubber, and liquid EPDM rubber, and has a viscosity of 50 to 2500 cps; (12) The liquid crystal epoxy resin is selected from any one or two of biphenyl liquid crystal epoxy resin and aromatic ester liquid crystal epoxy resin; (13) The terminal-modified polydiphenylsiloxane is a polydiphenylsiloxane containing olefin groups, terminal hydroxyl groups or silanol groups at both ends, and has a viscosity of 10 to 50 cps; (14) The nano core-shell structure powder grafted with the surface modifier is a nano spherical powder particle with non-polar groups on the surface.
3. The liquid metal sandwich thermally conductive gel sheet according to claim 2, characterized in that: Includes one or more of the following characteristics: 2a) The single metal is selected from any one of gallium, indium, tin, mercury, and cesium; the binary alloy is selected from any one of gallium-indium alloy, gallium-tin alloy, gallium-mercury alloy, gallium-cesium alloy, and tin-indium alloy; the ternary alloy is selected from any one of gallium-indium-tin alloy, gallium-indium-mercury alloy, gallium-indium-cesium alloy, gallium-tin-mercury alloy, gallium-tin-cesium alloy, gallium-mercury-cesium alloy, gallium-sodium-potassium alloy, and tin-indium-tin alloy; the multi-element alloy is one of the low-melting-point multi-element alloys prepared by any one or more of gallium, tin, silver, copper, aluminum, or chromium and any one of the above ternary alloys; 4a) the nanofiller is selected from one-dimensional nanofillers with a length of 10 to 100 μm and a diameter of 10 to 100 nm, and the one-dimensional nanofiller includes any one or more of carbon nanotubes, nanosilver wires, and nanozinc oxide wires; 4b) The inorganic functional filler comprises any one or more of alumina, aluminum nitride, boron nitride, diamond, and aluminum hydroxide; the particle size of alumina is selected from one or more of 0.2 μm, 1 μm, 10 μm, 40 μm, 70 μm, and 120 μm; the particle size of aluminum nitride is selected from one or more of 0.2 μm, 1 μm, 10 μm, 40 μm, 80 μm, and 120 μm; the lateral size of boron nitride is selected from one or more of 1 μm, 5 μm, 10 μm, and 20 μm; the particle size of diamond is selected from one or more of 1 μm, 5 μm, 10 μm, 40 μm, and 70 μm; the particle size of aluminum hydroxide is selected from one or more of 1 μm, 10 μm, and 30 μm; 14a) The powder particles in the nano-spherical powder particles are any one of aluminum oxide, silicon oxide, and magnesium oxide, and the particle size of the powder particles is 10 to 100 nm.
4. A method for preparing the liquid metal sandwich thermally conductive gel sheet according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Put component A and component B into a mixing tube respectively, mix them evenly according to the proportion through a dispensing machine, and dispense them on the substrate to obtain the first layer of thermal conductive gel; Step 2: Printing liquid metal on the first layer of thermal conductive gel by screen printing to obtain a liquid metal interlayer; Step 3: Repeat the operation of step 1 to obtain a second layer of thermally conductive gel, that is, a liquid metal sandwich thermally conductive gel sheet.
5. The method for preparing the liquid metal sandwich thermally conductive gel sheet according to claim 4, characterized in that: It also includes one or more of the following features: (1) Component A and component B are mixed evenly in a mass ratio of 1:1 using a dispensing machine; (2) The dispensing is performed in a certain shape; (3) The substrate is an aluminum plate.
6. The method for preparing the liquid metal sandwich thermally conductive gel sheet according to claim 4, characterized in that: The preparation method of component A comprises the following steps: (a) mixing the double-terminal vinyl polydimethylsiloxane, the double hydrogen-bond functional polydimethylsiloxane, the styryl siloxane, the terminal-modified polyhedral oligomeric silsesquioxane and the compatibilizer by a high-speed disperser to obtain a first mixture; (b) pouring the first mixture into a planetary mixer, adding nanofiller, and stirring evenly to obtain a second mixture; (c) adding the inorganic functional filler into a planetary mixer three times, and stirring evenly after each addition; (d) adding an antioxidant, vacuum extraction, and stirring to obtain component A.
7. The method for preparing the liquid metal sandwich thermally conductive gel sheet according to claim 5, characterized in that: It also includes one or more of the following features: (a1) In step (a), the material temperature during the mixing process is 20-30° C., the stirring rate is 1000-2000 rpm, and the stirring time is 15-25 min; (b1) In step (b), the material temperature during stirring is 20-30° C., the stirring rate is 200-300 rpm, and the stirring time is 10-14 min; (c1) In step (c), the material temperature during stirring is 20-30° C., the stirring rate is 200-300 rpm each time, and the stirring time is 20-30 min each time; (d1) In step (d), the material temperature during stirring is 20-30° C., the stirring rate is 400-500 rpm, and the stirring time is 30-40 min; (d2) In step (d), the vacuum degree of the vacuum extraction is below -0.08 MPa.
8. The method for preparing the liquid metal sandwich thermally conductive gel sheet according to claim 4, characterized in that: The preparation method of component B comprises the following steps: 1) mixing double-terminal vinyl polydimethylsiloxane, double hydrogen-bond functional polydimethylsiloxane, catalyst, liquid rubber, liquid crystal epoxy resin, terminal-modified polydiphenylsiloxane, surface modifier-grafted nano core-shell structure powder and compatibilizer in a high-speed disperser to obtain a third mixture; 2) Pour the third mixture into a planetary mixer, and add the inorganic functional filler into the planetary mixer three times, stirring evenly after each addition; 3) Add antioxidant, stir evenly, and extract under vacuum to obtain component B.
9. The method for preparing the liquid metal sandwich thermally conductive gel sheet according to claim 8, characterized in that: It also includes one or more of the following features: 1a) In step 1), during the mixing process, the material temperature is 20-30°C, the stirring rate is 1000-2000 rpm, and the stirring time is 15-25 min; 2a) In step 2), the material temperature during stirring is 20-30°C, the stirring rate is 200-300 rpm each time, and the stirring time is 20-30 min each time; 3a) In step 3), the material temperature during stirring is 20-30°C, the stirring rate is 400-500 rpm, and the stirring time is 30-40 min; 3b) In step 3), the vacuum degree of the vacuum extraction is below -0.08 MPa.